Perception and marketing / Hamdan Hassan - Hassan, Hamdan (Universiti Teknologi MARA, Pahang, 1988)
Each and everyone of us are 'short-changed' in what we see, hear, smell, touch and taste. In short, we are all with 'short perspectives'. The field of marketing capitalise on this understanding and are well demonstrated by what they do in promoting their products. Consumer activist does. not see the way a marketing man sees it.. What they are fighting for are for the 'longer perspectives' demanding the producers to give a better chance and 'more time' for consumers to see more of the products, tell more, have a chance to smell· it and if possible Lo taste it. Is it possible? Readers I hope are not 'short-changed' by my argument that seems to favour marketing. Hope you can spare me some kind thoughts. As a consumer you might have your reasons. And as a marketeer I have mine. But first surely you want to know how 'perception' is being defined by marketing people.